Eschatologia i epikureizm w starożytnym świecie: Julian Kułakowski o ludzkiej naturze w mitologii grecko-rzymskiej = Eschatology and epicureanism in the ancient world: Julian Kułakowski on the human nature in the greco-roman mythology - Puczkow, Andriej (Zielona Góra: Lubuskie Towarzystwo Naukowe)
Julian A. Kułakowski (1855-1919), Professor of the Roman rhetoric on the Imperial St. Włodzimierz?s University, Russified Pole, gave two public lectures in Kiev, one was about Lucretius (in 1887), the second one about Epicurus (in 1889). In 1899 he published the book titled: "Death and immortality in the ancient Greeks` images". Taken together, they are probably the first in the Russian humanities historico-philosophical views that concern the process of the integration of the form of Greco-Roman world view into eschatology and epicureanism at that time, views that at the turn of the XIX and XX century were moderated by decadent (tu brakuje słowa w polskim abstrakcie) of the intellectuals of the Silver Age.
Keywords: Kułakowski, Julian (1855-1919); eschatologia antycznej Grecji; Epikur (filozof grecki; 341 p.n.e.-270 p.n.e.); epikureizm; mitologia grecka; mitologia rzymska; eschatology; ancient Greece; Epicurus; Epicureanism; the Ancient Greece Mythology; the Roman Mythology